Removal of basic fuchsin from aqueous solutions by low-cost peanut shells adsorption in a fixed bed column - Amina Lahmara; Zhour Hattaba; Radia Zerdoum; Amina Berredjem; Ridha Djellabia; Kamel Guerfia (Desalination and Water Treatment, 2020)
The current study aims to valorize a raw peanut shell powder (PSP) as an innovative biomaterial for the recovery of basic fuchsin (BF) from the water via a dynamic adsorption process. In particular, the influence of some operating parameters such as flow rate, bed height, BF concentration, pH of the solution, ionic strength and temperature on the breakthrough curve was studied. The Fourier transform infrared spectroscopy analysis confirms the dominant presence of cellulose, hemicellulose, lignin and xylene in PSP which is in good agreement with the X-ray diffraction analysis. Scanning electron microscopy images show that PSP has a morphology rich with hollow cavities with a high roughness that is favorable to the binding of organic molecules. The value of the Zeta potential (2.30 mV) confirms a positive charge of the material surface which is in good agreement with the curve pHPZC (PZC – point of zero charge). The adsorption tests showed that overall, an optimal adsorption efficiency of 98% can be achieved for a flow rate of 4 mL min–1, an initial concentration of 5 mg L–1, a bed height of 55 mm, a pH 6 and a temperature of 298 K. Four kinetic models (Thomas, Yoon–Nelson, Bohart–Adams, and Wolborska) were proposed to predict the breakthrough curves using non-linear regression and determine the characteristic parameters of the column, namely the kinetic constants of Thomas (3.14 × 10–3 ml mg–1 min–1) and Yoon–Nelson (13.62 × 10–3 min–1), the sorption rate coefficient of Bohart–Adams (2.86 × 10–3 ml mg–1 min–1) and the external mass transferbkinetic coefficient of wolbrska (15.90min-1). The results indicate that the four proposed models are adequate for describing the breakthrough curve and that the data is in good agreement with the bed depth service time model with some limitations.